El cine súper 8 en México. 1970-1989 - Lusnich, Ana Laura (Imagofagia, 2021)
Sobre Vázquez Mantecón, Álvaro. El cine súper 8 en México. 1970-1989. México: Filmoteca UNAM, 2012, 337 pp., ISBN 978-607-02-3910-6. Palabras clave: reseña, Vázquez Mantecón, Álvaro, El cine súper 8 en México. 1970-1989